جهود الشيخ محمد رشيد رضا في التفسير الموضوعي-الموضوع القرآني في سورتي النساء و المائدة أنموذجا- - بن علي, نذير; زايري, يحي (University of eloued جامعة الوادي, 2021)
"تناول هذا البحث جانبا مهما من أنواع التفسير وهو التفسير الموضوعي؛ وقد ارتكز البحثُ على أحد أئمة التفسير في العصر الحديث، وهو الإمام محمد رشيد رضا من خلال بيان جهوده في التفسير الموضوعي والموضوع القرآني خصوصا في سورتي النساء والمائدة في كتابه تفسير المنار, حيث قمنا من خلال هذه الدراسة بالوقوف على تطبيقات الشيخ محمد رشيد رضا في التفسير الموضوعي والموضوع القرآني خصوصا، وسنحاول الإجابة عن الإشكاليات التالية: فيما تتمثل جهود الشيخ رشيد رضا في خدمة التفسير الموضوعي والموضوع القرآني خصوصا؟, وما هي الدوافع التى جعلت الشيخ رشيد رضا يُضمّن تَفسيرهُ موضوعاتِ التفسير الموضوعي؟, وهل للشيخ رشيد رضا رؤية خاصة ومنهج معيّن للموضوع القرآني؟, وما مدى اتفاق أمثلة المنار التطبيقية مع الخطوات العلمية النظرية للموضوع القرآني التي أقرها الخالدي؟, وتُوِّجَ البحث في ختامه ببعض النتائج والتوصيات المتوصل إليها لعل أهمها:يعتبر تفسير المنار من أوائل كتب التفسير في العصر الحديث التي تضمنت موضوعات التفسير المووضوعي, اعتنى صاحب المنار بالموصوع القرآني و السورة الموضوعية عناية كبيرة, اهتم صاحب المنار بعلم المناسبات و مقاصد القرآن موضفا إياهما في خدمة الموضوع القرآني وتقريب فهم معاني القرآن؛ وكان من جملة التوصيات لطلبة العلم والباحثين هو مواصلة وإكمال دراسة منهج محمد رشيد رضا في الوحدة الموضوعية للسورة والمصطلح القرآني؛ ودراسة عنايته بالموضوع القرآني لأجزاء أخرى من القرآن الكريم, وكذا دراسة آراء محمد رشيد رضا الفقهية من خلال تفسير المنار. ""This topic deals with an important aspect of interpretation which is objective interpretation and the research was based on one of the imams of interpretation in the modern era who is imam Mohammed Rida .Through his efforts in objective interpretation and the Quranic subject ,especially in ""surat Al Nisa and Al Maidah"" in his book ""Tafsir al Mandar"" and Through his study ,we stand on the applications of sheikh Mohammed Reda in the objective interpretation and the Quranic subject in particular and we will try to answer the following problems: What are the efforts of sheikh Mohammed Rida in serving objective interpretation and the Quranic subject in particular ?And what are the motives that made Sheikh Mohammed Rachid Rida took his interpretation of the topics of objective interpretation ?? And does sheikh Mohammed Rachid Rida have a special vision and a specific approach to the Quranic subject ?And to which extent applied exemples of AlManar agree with the theoritical scientific steps of the Quranic subject approved by Alkhalidi? Finally,the research concluded with some results and recomman-dations .The most important of them;-interpretation of AlManar is considred one of the first books of interpretation in the modern era that included topics of objective interpretation.The owner of AlManar took great care of the subject with the Quranic subject and the objective Surah,as its owner AlManar was concerned with the science of occasions and the purposes of the Quran, adding them to the service of the Quranic subject,and bring closer understanding of the meanings of the Quran and among the recommandations for students and researchers was to continue and complete the study of Mohammed's Rachid Rida approach in the substantive unity of the Surah and the Quranic term.And a study of its concern with the subject of parts of the holy Quran as well as studying the jurisprudentiel views of Mohammed Rida Through the interpretation of Al Manar. "
علوم قرآن
Keywords: التفسير الموضوعي- محمد رشيد رضا-الموضوع القرآني; interpretation which-Mohammed Rachid Rida